Modifiable lifestyle and metabolic risk factors for colorectal polyps: a systematic review and meta-analysis - Lei, Yue; Cai, Zihong; Zheng, Mengli; Deng, Yunfan; Li, Shirui; Li, Xiuyang; Dai, Sheng (Frontiers in Public Health, 2025)
ObjectiveTo evaluate associations between unhealthy lifestyles, metabolic diseases, and colorectal polyps, with emphasis on subtype-specific effects.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and SinoMed (up to July 2024) for studies reporting odds ratios (ORs) of colorectal polyps associated with lifestyle or metabolic factors. Heterogeneity was quantified using I (2) statistics, with random-effects models applied as the primary analytical approach. Subgroup analyses were conducted to investigate potential effect modifiers, and meta-regression was performed to explore continuous sources of heterogeneity, while sensitivity analyses and funnel plots evaluated robustness and bias.ResultsAlcohol (OR = 1.63, 95%CI:1.48-1.78), high-fat diet (OR = 1.45, 95%CI:1.33-1.57), and smoking (OR = 1.79, 95%CI:1.69-1.90) significantly increased polyp risk across subtypes. Smoking showed subtype- and region-specific effects, with the highest risk for sessile serrated lesions (SSLs; (OR = 3.06, 95%CI:2.41-3.90)) and in the US, South Korea, and Israel. Type 2 diabetes had the strongest metabolic association (OR = 2.17,95%CI:1.82- 2.60), followed by hyperlipidemia (OR = 1.50, 95%CI:1.32-1.70) and hypertension (OR = 1.33, 95%CI:1.10-1.61). Heterogeneity stemmed from pathological classification and geographic variation, with no significant publication bias.ConclusionUnhealthy lifestyles (alcohol, high-fat diet, smoking) and metabolic diseases (type 2 diabetes, hyperlipidemia, hypertension) independently increase colorectal polyp risk, with smoking demonstrating pronounced subtype and regional variability. These findings can inform the development of risk-stratified screening protocols and targeted public health interventions.